MENAKAR EFEKTIVITAS DIGITAL MARKETING VIA INSTAGRAM - Putu Dian Restiana Dewi; Gede Sri Darma (JURNAL ILMIAH EDUNOMIKA, 2022)
The phenomenon of economic globalization worldwide encourages almost all levels of society to be connected via the internet and sosial media. In business development, an effective marketing strategy is needed to welcome these technological advances. The more technological advances are developing, the advancement of sosial media such as Instagram relies on user-uploaded images to share, like, and comment. This study aimed to determine the marketing effectiveness of clothing and culinary entrepreneurs using sosial media Instagram in Bali Province. The research design used is qualitative research with the type of phenomenological research. The samples in this study were four clothing and culinary business informants who used sosial media Instagram as promotional media, which took purposively. Data collection techniques used were in-depth interviews, field observations and checking related documents. Based on the research results, using Instagram sosial media to promote clothing and culinary businesses is quite effective and brings additional income for informants.